Negosiasi Kekuasaan Tersembunyi: Analisis Ekologi Politik Militer di Negara-Negara Asia Selatan - Syarifah Fadhilah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article analyzes Hidden Power Negotiations through the lens of Military Political Ecology in South Asia, a region characterized by historical rivalries and extreme climate vulnerability. The research objective is to uncover how military power and geopolitical competition (US-China) intrinsically shape and are shaped by the environmental crisis. The research method uses a qualitative approach with a Political Ecology analysis study of literature and strategic documents. The findings indicate that power negotiations operate through military alliances (China-Pakistan) and strategic infrastructure projects, which militarize environmental issues. This phenomenon transforms resource scarcity into a justification for military mobilization, which exacerbates socio-ecological inequality and neglects grassroots environmental peacebuilding solutions. In conclusion, the region faces an Ecological Security Dilemma, demanding a shift from hard power dominance toward inclusive environmental governance to achieve sustainable stability.